The North Atlantic trade of Hamburg (c. 1400–1650) (AmS-Skrifter, 2020)
Hamburg was the main north German town trading with the western North Atlantic region in the period between 1450 and 1650. Other towns, such as Lübeck, Wismar and Rostock also called at Bergen, but the contact of German seafaring merchants with Iceland was dominated by men from Hamburg. Even after the closing of the island to all except Danish-Norwegian merchants by the Danish kings, the trade with Hamburg continued and partly bypassing the warehouse in Glückstadt. The main export commodities were grain and cloth, while back came fish and sulphur, besides some articles of minor significance. The Shetland trade also had some importance for the Hamburg merchants, importing fish and exporting grain and fishing material. In general, the North Atlantic trade was of minor importance in the total of the Hamburg trade which was dominated by transactions with western (Holland, England, France) and south-western (Portugal, Spain) Europe. The highest profits were made in that sphere.